Hydrogenation of 3-hydroxypropanal to 1, 3-propanediol over a Cu–V/Ni/SiO2 catalyst. (26th July 2017) - Li, Li-Jun; Yi, Wen-Jun; Liu, Tian-Wei; Huang, Chen; Li, An; Luo, Cai-Wu; Chao, Zi-Sheng
Abstract : The introduction of Cu–V into the Ni/SiO2 catalyst promoted the reduction of Ni 2+ to Ni 0 and the generation of active hydrogen species and thus increased the yield of 1, 3-PDO. Abstract : A Ni-based catalyst modified with copper and vanadium (5Cu–20V/30Ni/SiO2 ) was synthesized and employed in the hydrogenation of 3-hydroxypropanal (3-HPA) to 1, 3-propanediol (1, 3-PDO). Catalysts were systematically characterized via XRD, TEM, HRTEM, SAED, H2 -TPD, N2 physisorption, H2 -TPR, and XPS. It was indicated that the addition of Cu and V not only promoted the reduction of Ni 2+ species and the generation of active hydrogen species, but also increased the dispersion of Ni species and the interaction between Ni particles and SiO2 . The catalytic performance evaluation showed that the (5Cu–20V/30Ni/SiO2 ) could provide the largest yield of 1, 3-PDO (above 76.8%) and highest TOF (4.32 × 10 3 s −1 ). The structure–activity relationship was clarified according to the characterization results. The optimized reaction conditions over the 5Cu–20V/30Ni/SiO2 catalyst were obtained as the reaction temperature of 80 °C, a H2 pressure of 2.0 MPa (H2 ), and an LHSV of 0.4 h −1 . The employment of non-noble metals, the relatively low pressure of H2, and the relatively high yield of 1, 3-PDO make 5Cu–20V/30Ni/SiO2 an efficient and economic catalyst that may have potential applications in industry.